Carotid intima-media thickness is an independent predictor of all-cause mortality and cardiovascular morbidity in patients with diabetes mellitus type 2 and chronic kidney disease - Athanasios Roumeliotis (Renal Failure, 2019)
Background: Intima-Media-Thickness of the carotid artery wall (cIMT) is a strong predictor of cardiovascular (CV) disease. The aim of this study was to investigate the significance of cIMT as an independent prognostic factor for CV morbidity and mortality in patients with chronic kidney disease (CKD) and diabetes mellitus type 2 (DM2). Methods: The study included 142 diabetic patients in different stages of CKD. Patients were categorized into two groups according to low (≤0.86 mm) or high cIMT (>0.86 mm), respectively. CV events and death from all causes were registered during a seven-year follow-up. Results: Mean age, BMI and duration of diabetes were 68 years (range: 45–90), >30 kg/m2 and 15 years (range: 5–40), respectively. Patients with increased cIMT were older, suffered from a lower estimated glomerular filtration rate (eGFR), peripheral atherosclerosis and plaque presence in either carotid artery. Increased BMI (beta= −0.29, p = .01), lower eGFR (beta = 0.353, p = .003) and male gender (beta= −0.339, p = .005) were found to predict increased cIMT. Predictors of all-cause mortality in Cox proportional hazard models were low eGFR and high cIMT with HR = 0.96 (CI = 0.94–0.98), p < .001 and HR = 2.9 (CI = 1.03–7.99), p = .04, respectively. The risk of future CV event was determined by albuminuria and cIMT with HR = 1 (CI = 1.0–1.0), p < .001 and HR = 2.04 (CI = 1.1–3.78), p = .02, respectively. Patients with high cIMT presented significantly higher all-cause mortality and a new CV event (p = .005/p = .018, respectively). Conclusions: cIMT is a strong and independent predictor of CV morbidity and mortality, and should be considered a valuable tool for the stratification of CV risk in patients with CKD and DM2.